Structural, antioxidant, and immunomodulatory activities of an acidic exopolysaccharide from Lactiplantibacillus plantarum DMDL 9010 - Huang, Yan-yan; Wu, Jia-min; Wu, Wei-tong; Lin, Jia-wei; Liang, Yan-tong; Hong, Zhen-zhen; Jia, Xiang-ze; Liu, Dong-mei (Frontiers in Nutrition, 2022)
This study investigated the structural, antioxidant, and immunomodulatory activities of acidic exopolysaccharide (EPS-LP2) isolated from Lactiplantibacillus plantarum DMDL 9010. EPS-LP2 is composed of fucose (Fuc), arabinose (Ara), galactose (Gal), glucose (Glc), mannose (Man), and D-fructose (Fru) with a molar ratio of 0.13: 0.69: 8.32: 27.57: 62.07: 0.58: 0.46, respectively. Structural analysis of EPS-LP2 exhibited a smooth irregular lamellar surface, rod-like structure with swollen ends and slippery surfaces, and good thermal stability. Based on the methylation and NMR analysis, sugar residues including t-Manp, t-Glcp, 2-Manp, 6-Galp, 6-Glcp, and 4-Glcp were found to exist in EPS-LP2. In the 50∼400 μg/ml range, EPS-LP2 showed negligible neurotoxicity to RAW264.7 cells. Moreover, EPS-LP2 could protect RAW264.7 cells from oxidative injury by lowering the generation of reactive oxygen species (ROS), malondialdehyde (MDA), and the secretion of lactate dehydrogenase (LDH). In contrast, an increase in superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), and the concentrations of glutathione (GSH) were observed. Immunoreactivity assays showed that EPS-LP2 could suppress the expression of NO, tumor necrosis factor-α (TNF-α), and interleukin 6 (IL-6) and inhibit the activation of the mitogen-activated protein kinase (MAPK)/nuclear factor-κB-gene binding (NF-κB) cell pathway. Conclusively, EPS-LP2 could be a potential natural antioxidant and immunomodulatory agent in functional foods and medicines.